Effect of N-(7-dimethylamino-4-methyl-3-coumarinyl) Maleimide on Fermentation of Citric Acid by Aspergillus niger NCIM-2101 - Chaurasia, Umesh Prasad (Journal of Nepal Chemical Society, 2018)
Available with Full text.